Insights into the genetic variation profile of tprK in Treponema pallidum during the development of natural human syphilis infection. - Dan Liu; Man-Li Tong; Yong Lin; Li-Li Liu; Li-Rong Lin; Tian-Ci Yang (Public Library of Science (PLoS), 2019)
Background Although the tprK gene of Treponema pallidum are thought to play a critical role in the pathogenesis of syphilis, the profile of variations in tprK during the development of human syphilis infection have remained unclear. Methods/principal findings Through next-generation sequencing, we compared the tprK gene of 14 secondary syphilis patients with that of 14 primary syphilis patients, and the results showed an increased number of variants within the seven V regions of the tprK gene in the secondary syphilis samples. The length of the sequences within each V region also presented a 3-bp changing pattern. Interestingly, the frequencies of predominant sequences within the V regions in the secondary syphilis samples were generally decreased compared with those found in the primary syphilis samples, particularly in the V7 region, where a frequency below 60% was found in up to 57% (8/14) of all secondary samples compared with 7% (1/14) of all primary samples. Moreover, the number of minor variants distributed between frequencies of 10 and 49.9% was increased. The alignment of all amino acid sequences within each V region of the primary and secondary syphilis samples revealed that some amino acid sequences, particularly the amino acid sequences IASDGGAIKH and IASEDGSAGNLKH in V1, were highly stable. Additionally, the amino acid sequences in V6 also exhibited notable intrastrain heterogeneity and were likely to form a strain-specific pattern at the interstrain level. Conclusions The identification of different profiles of the tprK gene in primary and secondary syphilis patients indicated that the tprK gene of T. pallidum undergoes constant variation to result in the best adaptation to the host. The highly stable peptides found in V1 are likely promising potential vaccine components. The highly heterogenetic regions (e.g., V6) could help to understand the role of tprK in immune evasion.